mcr-1 and blaKPC-3 in Escherichia coli Sequence Type 744 after Meropenem and Colistin Therapy, Portugal - Marta Tacão; Rafael dos Santos Tavares; Pedro Teixeira; Inês Roxo; Elmano Ramalheira; Sónia Ferreira; Isabel Henriques (Emerging Infectious Diseases, 2017)
Escherichia coli Ec36 was recovered from a patient in Portugal after treatment with meropenem and colistin. Besides an IncF plasmid with Tn1441d-blaKPC-3, already reported in clinical strains in this country, E. coli Ec36 co-harbored an IncX4::mcr-1 gene. Results highlight emerging co-resistance to carbapenems and polymyxins after therapy with drugs from both classes.